2021
DOI: 10.1093/ibd/izab165
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum Exposure to Biologic Therapy Does Not Impact Postpartum Wound Healing in Women With IBD

Abstract: Background Inflammatory bowel disease (IBD) commonly affects women during childbearing years and often requires antepartum therapy. Data regarding effects of biologic exposure on delivery outcomes are limited. We explored whether peripartum biologic exposure impacts wound healing following cesarean section (C-section) and vaginal delivery (VD) in IBD patients. Methods Pregnancy and IBD data from the IBD Preconception and Preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The secondary outcome of wound-related complications in participants using anti-TNF agents was not significantly elevated (OR=1.18, 95% CI 0.83 to 1.68). Another study identified no greater risk of wound infection with peripartum biologic therapy (n=100)187 or with intra-abdominal surgery 188. Although there are no data to guide the timing of therapy resumption after delivery, we consider it reasonable for this to happen after delivery and before discharge if there are no contraindications.…”
Section: Appropriate Statementsmentioning
confidence: 94%
“…The secondary outcome of wound-related complications in participants using anti-TNF agents was not significantly elevated (OR=1.18, 95% CI 0.83 to 1.68). Another study identified no greater risk of wound infection with peripartum biologic therapy (n=100)187 or with intra-abdominal surgery 188. Although there are no data to guide the timing of therapy resumption after delivery, we consider it reasonable for this to happen after delivery and before discharge if there are no contraindications.…”
Section: Appropriate Statementsmentioning
confidence: 94%
“…Although vaginal delivery has not affected longer term J-pouch functioning, continued pelvic floor pressure and sphincter compromise can affect continence, which may already be present before pregnancy (85,86). It should be noted that many patients experience a grade 1 or 2 tear, especially on their first delivery, but the risk of a grade 3-4 tear remains less than 5% (87). Given the potential impact of perineal trauma, operative assisted vaginal delivery should be carefully considered and, if possible, converting to a cesarean section may be a better option in some patients.…”
Section: Mode Of Deliverymentioning
confidence: 99%
“…By planning infusion intervals according to the delivery date, patients would be able to get their infusions at the hospital at the time of delivery. Biologic exposure, specifically infliximab, within 24-48 hours of delivery did not increase the risk of poor wound healing after cesarean or vaginal delivery (87). Consideration for moving infusion-based therapies to the home is often preferred and should be organized before delivery.…”
Section: Postpartum Managementmentioning
confidence: 99%
“…Lastly, it should be noted that many patients experience a grade 1 or 2 tear especially on their first delivery but the risk of a grade 3–4 tear remains less than 5% 49. Complicated CD, peripartum disease activity and deescalation of biologics during pregnancy and after delivery are associated with postpartum disease activity and is not encouraged 50…”
Section: Introductionmentioning
confidence: 99%